Comparative study on correctness and time taken of test case generation using EFG and BXT techniques for GUI application - Nser Brka, Mostafa (2015)
The previous decade witnessed the increased popularity and rapid development of graphical user interface (GUI). GUI is a type of computer– human interface thatallows users to communicate with their computers. This interface has significantly contributed to the popularity of recently developed software applications. Given the importance of working under an error-free GUI, the correctness of such GUI must be tested at all times. GUI testing involves checking the screens for controls, such as menus, buttons, icons and all types of bars, including tool bars, menu bars, dialog boxes and software windows. Event Flow Graph (EFG) and Behavior ExplorerTesting (BXT) are two of the techniques used to generate test cases on GUIcomponents. The correctness and time required for these two techniques to generate GUI test cases are compared in this project by using the techniques in Paint and Present applications. EFG and BXT obtained correctness rates of 9.61% and 36.81% respectively for the paint application and 5.18% and 39.33% respectively for the Present application. Therefore, BXT exhibits more correctness than EFG. In term of elapsed time, EFG and BXT spent 0.16 millisecond (ms) and 0.18 ms in the paint application respectively and 0.14 millisecond (ms) and 0.17 millisecond (ms) in the Present application respectively. Therefore, EFG is slightly faster than BXT in generating test cases. Overall, BXT is better than EFG in generating GUI test cases.